Spatiotemporal Pattern of Gadodiamide-Related T1 Hyperintensity Increase Within the Deep Brain Nuclei. Issue 12 (December 2018) - Marie, Guillaume P.O.; Pozeg, Polona; Meuli, Reto A.; Maeder, Philippe; Forget, Joachim
Abstract : Objectives: The purpose of the study was to systematically evaluate the precise spatial and temporal pattern of gadolinium-related changes in T1-weighted signal intensity on unenhanced magnetic resonance (MR) images, occurring in the deep brain nuclei of adult patients exposed to at least 10 consecutive doses of gadodiamide. Materials and Methods: In this monocentric retrospective longitudinal study, we analyzed the brain MR images of 30 patients (12 women, 18 men; mean age, 43 ± 11.6 years) acquired between December 1998 and March 2008. We drew the regions of interest in the dentate nucleus, globus pallidus, putamen, pulvinar, ventral posterior nucleus of the thalamus, superior colliculus, substantia nigra, and white matter on unenhanced T1-weighted images. Each region of interest's mean signal intensity was normalized by the mean intensity of the pons. The normalized signal intensities were measured at the baseline before first gadodiamide administration and at each of 10 successive MR imaging examinations. We used linear mixed effects models to analyze the data. Results: We observed a significant linear increase of signal intensity ratios across 10 successive gadodiamide administrations (all basal nuclei were significant at P < 0.001, except the ventral posterior thalamus, where P < 0.05), with the fastest signal intensity increase in the dentate nucleus (B = 0.010), followed by the globus pallidus (B = 0.0068), putamen (B = 0.0063), pulvinar (B = 0.0062), superior colliculus (B = 0.0057), substantia nigra (B = 0.0034), and ventral posterior nucleus of the thalamus (B = 0.0031). No significant signal increase was observed in the white matter ( P > 0.05). Conclusions: Multiple consecutive administration of gadodiamide is associated with an increase in T1-weighted hypersignal on the unenhanced scans, displaying a gradual and nonuniform pattern across different deep brain nuclei, including the ventral posterior thalamus, which was used as a reference tissue in previous studies.